Politiques canadiennes de l’énergie et libre-échange – ou le sacrifice d’Iphigénie - Duquette, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1988)
This study looks into the federal government' s relinquishment of its 1980 energy policy known as the National Energy Programme. Such a sacrifice was made in the name of free trade between Canada and the U.S. Indeed, it is suggested that for the Conservatives, their deregulation of the energy industry for the sake of the economic integration of North America has served as the very proof of free trade. Hence also the end of the Foreign Investment Review Agency symbol of Canadian nationalism. For the free trade negotiations to be concluded, Ottawa needs to establish a common front with the provinces. This new context is in agreement with the "national reconciliation" policy extolled by the Tories soon after they came to power. In the name of a more decentralized Federation, they would surrender much in order to stimulate trade between the regions and the American market. This appears to them as the best way to boost the economy to a point which is already reached by our neighbours in the south. Thus the two projects, i.e. a complete redefinition of the energy policy and rapprochement with Washington, are being seen through simultaneously, in a spirit of compromise. In handing over to the provinces the administration of their off shore territories, and going as far even as to promote their traditional stance regarding the canadian energy policy, Alberta being a case in point, the government espouses a particular style of relationship with the industry. So as to bring Canada to par with current practices in the U.S., it brings forth its objective of "privatisation" which is in accordance with the neo-conservative credo: the subsidization of industry, deregulation, sharing out of the energy industry to the advantage of the private sector, the eventual privatization of Petro Canada. In this study, a first framework for analysis of those phenomena, with regard to the current negotiations between Canada and the US, is proposed.